Visual Da Vinci extension for real robot control - Champredonde, Raúl (1998)
Visual DaVinci is a visual programming language whose purpose is programming learning. The development environment allows the implementation, execution and debugging of the algorithms specified with the mentioned language. The implementation of an algorithm may be carried out in a conventional way, that is, by writing each of its instructions, or by means of a visual diagram, which can in turn be used as a designing tool. Both implementations may be indistinctly used at any moment of the development of a program. An extension that allows to control a real robot with moving capacity and which is able to execute the algorithms implemented in Visual DaVinci, is described in this paper.